GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 241 species occurrences available in GBIF matching the query: TaxonKey: Centris flavifrons (Fabricius, 1775) HasCoordinate: true HasGeospatialIssue: false. The dataset includes 241 records from 7 constituent datasets: 15 records from Bee Biology and Systematics Laboratory. 4 records from Illinois Natural History Survey Insect Collection. 98 records from Coleção de Entomologia do Laboratório de Biologia Vegetal. 15 records from Coleção Entomológica Paulo Nogueira-Neto - IB/USP. 76 records from Coleção Entomológica do Depto. de Sistemática e Ecologia. 25 records from Snow Entomological Museum Collection. 8 records from Colección de artrópodos del PNN Gorgona - Museo de Entomología de la Universidad del Valle (MUSENUV).
Keywords: GBIF; biodiversity; species occurrences